2019
DOI: 10.1016/j.biopsych.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Behavioral, Neuroanatomical, and Germline Influences of Intergenerational Stress

Abstract: BACKGROUND:Stressors affect populations exposed to them as well as offspring. Strategies preventing the intergenerational propagation of effects of stress would benefit public health. Olfactory cue-based fear conditioning provides a framework to address this issue. METHODS:We 1) exposed adult male mice to an odor, acetophenone (Ace) or Lyral (parental generation [F0]-Exposed), 2) trained mice to associate these odors with mild foot shocks (F0-Trained), and 3) trained mice to associate these odors with mild foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 51 publications
5
26
0
Order By: Relevance
“…Training mice to associate a specific odor (eg, Odor A) with a mild foot‐shock results in these mice developing fearful behavior toward Odor A and possessing increased neuroanatomical expression of odorant receptors that detect Odor A . From an intergenerational perspective, we have demonstrated that after mice have been exposed to Odor A + shock conditioning their naïve offspring possess a sensitivity to Odor A and increased neuroanatomical expression of odorant receptors that detect Odor A . Ours are not the only studies to have reported intergenerational imprints of parental olfactory experience.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…Training mice to associate a specific odor (eg, Odor A) with a mild foot‐shock results in these mice developing fearful behavior toward Odor A and possessing increased neuroanatomical expression of odorant receptors that detect Odor A . From an intergenerational perspective, we have demonstrated that after mice have been exposed to Odor A + shock conditioning their naïve offspring possess a sensitivity to Odor A and increased neuroanatomical expression of odorant receptors that detect Odor A . Ours are not the only studies to have reported intergenerational imprints of parental olfactory experience.…”
Section: Introductionmentioning
confidence: 72%
“…F0‐Lyral treatment: Due to the position of MOR23‐GFP glomeruli on the olfactory bulb it is challenging to visualize and quantitate their size and instead we used western blotting to measure the GFP levels as we have performed in our previous publication (Figure S3B). We found a significant increase in GFP expression in the MOE of F1‐trained Lyral F0 sperm RNA animals compared with F1‐exposed Lyral F0 sperm RNA animals ( F = 7.19, P = .021, d R = 1.201) (Figure G,H) (full blots shown in Figure S6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations